Discipline and student achievement based on the management of Islamic education systems - MUNIFAH, K.; HAMIDA, U.; FIRMANSYAH, M.; HUDA, S.; MUAWANAH, A.; IRWANDANI, R. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This research is focused on developing disciplinary values in implementing good manners and morals in the school environment. Improving work culture based on discipline in the Islamic school (madrasas) environment is the main topic in this study. This research uses a qualitative approach and includes ex post facto research. The results of this study can be concluded that the overall work culture that appears from the attitudes and work behaviors of the madrasas community are: serving, innovative thinking, working hard, active learning, enthusiastic, grateful, confident, disciplined, independent, competitive, to obtain success and excellence. RESUMEN Esta investigación se centra en el desarrollo de valores disciplinarios en la implementación de buenos modales en el entorno escolar. Mejorar la cultura laboral basada en la disciplina en el entorno escolar islámico es el tema principal de este estudio. Esta investigación utiliza un enfoque cualitativo e incluye investigación ex post facto. Los resultados de este estudio pueden concluir que la cultura laboral general que surge de las actitudes y los comportamientos laborales de la comunidad madrasas son: servicio, pensamiento innovador, entusiasmo, agradecimiento, confianza, disciplina, independencia, competitividad, para obtener éxito y excelencia.